(untitled) (European Journal of Marketing and Economics, 2024)
Following the eradication of a domestic terrorist menace that severely disrupted the country for over thirty years, Sri Lanka has entered an era of rapid social and economic development where mass media can play a highly significant role in national transformation. Within this developmental process, an urgent need arises to study the specific role of advertising media in the sphere of cultural evolution, particularly because the unique nature and historical trajectory of Sri Lankan advertising culture heavily depend on traditional oriental cultural values. Because a cultural dimension—defined as a learned system of shared knowledge, attitudes, behaviors, beliefs, and norms—is an essential factor for understanding modern media environments, it must be rigorously evaluated; yet, sufficient academic emphasis has not yet been placed on how advertising functions as a core component in the conceptual development and broader cultural processes of Sri Lanka. Advertising within oriental cultural value settings remains a remarkably under-explored area of research across global disciplines, including media and communications studies, leaving a distinct gap in the literature that the authors of this paper actively attempt to fill. By deeply examining the direct effects of oriental cultural values on the contemporary advertising culture in Sri Lanka, this study ultimately aims to provide a framework that fosters the active cultivation and preservation of authentic Sri Lankan cultural values through more conscious, contextually aware concept development in modern commercial advertising.